State and Tendencies of General Disease Incidence of the Population Living in the Cities of Rostov Region - T. A. Kondratenko; L. F. Duz’; N. G. Tyutyun’kova; Yu. A. Ponomareova (Проблемы особо опасных инфекций, 2008)
Health of the population living in the cities of Rostov region was studied to detect priority non-infectious diseases really influencing the characteristics of general disease incidence of the population. These findings allow to correct therapeutic and prophylactic measures in pre-admission stage, to work out and take administrative decisions aimed at detection and treatment of patients with stated pathologies in pre-admission stage and prophylaxis among people included in risk groups.